GE_GERICHTE P/22495/2014 vom 14. Mai 2018 - GE Cour de justice (2018)
IN DUBIO PRO REO ; PRÉSOMPTION D'INNOCENCE ; MENACE(DROIT PÉNAL) ; INJURE ; SITE INTERNET ; TÉLÉPHONE ; EXEMPTION DE PEINE | CP.180.al1; CP.177.al1; CP.177.al3; CP.173.al4